Documentation of preoperative counselling for female sterilisation: a complete audit cycle. Issue 1 (1st January 2005) - Anderson, Judy; Gunn, Eleanor; Hunter, Mandy; Owen, Philip
Abstract : Background: Female sterilisation is a commonly performed gynaecological procedure that attracts a disproportionate number of complaints and litigation. Documentation of the key counselling issues provides an important record of the information given to the woman prior to undergoing sterilisation Methods: Auditable standards were obtained from published guidelines. After the initial audit of 100 cases a proforma was introduced in an effort to improve documentation. A re-audit of 50 cases was undertaken to ascertain compliance of documentation following the introduction of the proforma. Results: The proforma was used in 62% of cases and in all such cases documentation was 100% compliant with the auditable standards. Overall, documentation of standards pre- and post-proforma, respectively, was as follows (all the figures quoted are percentage values, with the range given in parentheses): 33 (24–43) vs 68 (53–80) for long-term alternatives, 94 (87–98) vs 78 (62–87) for irreversibility, 96 (90–99) vs 78 (64–88) for failure rate, 48 (38–58) vs 66 (51–79) for ectopic pregnancy risk if sterilisation fails, 39 (29–49) vs 66 (51–79) for the intended method, 67 (57–76) vs 66 (51–79) for operative risks and 37 (28–47) vs 64 (49–77) for continuing current contraception until sterilisation performed. Conclusions: Documentation of preoperative counselling for female sterilisation is often incomplete and does not comply with published recommendations. The introduction of a proforma resulted in a mixture of both improvement and deterioration of documentation. When the proforma was used, compliance with recommendations was 100%.